Assessing of soil compaction on different land used in Bintulu, Sarawak - Jamaluddin, Aiza Shaliha; Abdu, Arifin; Abdul Hamid, Hazandy; Jusop, Shamshuddin; Karam Singh, Daljit Singh; Karim, Md. Rezaul (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
Assessing land uses/land cover-induced changes in soil properties from natural forests to farmland are essential for addressing the issues of agricultural landscape sustainability. A study was conducted in the rehabilitated forest (RF), secondary forest (SF), oil palm (OP) and rubber plantation (RP) at Universiti Putra Malaysia Bintulu Campus, Sarawak in order to examine the effects of soil compaction on soil properties. Soil compaction was measured using fall-corn-type soil penetrometer until the depth of 50 cm. The results showed that the soil compaction was severe at RP and OP compared to SF and RF. The present study shows that soil compaction were affected by types of trees/different crops, soil managements, types of parent materials and climatic condition. Therefore, it is required to develop proper land use policy, sustainable soil management and cropping practices to combat the on ongoing soil degradation in the study area.